任务型教学法与对外汉语教学研究综述 - Ting, Hie Ling; Lam, Kai Chee (Journal of Maobi, 2025)
The Task-based Language Teaching method (TBLT) which also known as Task-based Approach (TBA) or Task-based Instruction (TBI) was proposed by Prabhu. It became popular in the 1990s, which earned the title of "The Age of Task". This teaching approach is applicable to second language or foreign language teaching. The application of TBLT method helps to mobilize learners' subjective initiative and enhance students' language creativity. The authenticity principle of the TBLT method enables learners to learn, use, and create language through participation in real-life situations. This paper briefly describes the application of the theoretical basis, teaching mode, and the roles of teachers and students of the TBLT in teaching Chinese as a foreign language. It also makes an evaluation and reflection on the application of task-based teaching in teaching Chinese as a foreign language based on previous research, aiming to provide reference for learning Chinese as a second language or foreign language.